Narrative perspective and focalisation in translating fictional narratives - Mozetič, Uroš (ELOPE (Ljubljana), 2004)
The main objective of this paper is to present the complex processes of the shifting of narrative perspective (point-of-view) and focus in translating English prose texts into Slovene. For that purpose, a narratological discourse analysis of James Joyce's story 'Eveline' (Dubliners) is introduced, drawing on K. M. van Leuven-Zwart's comparative and descriptive model. Th e model, which has been expanded by three additional categories - narrative mode, narrative perspective, and focalisation -, brings to the forefront the cause-and-eff ect relationship between the micro- and macrostructural shifts on the one hand, and the shifts in narrative perspective and focalisation on the other. Th e results obtained show that the model is empirically verifi able and repeatable. Th is means that it can also be used with other integral translations, particularly if translation shifts are subtle enough and/or consistent with the translator's dominant strategy and norm.
Keywords: angleščina; angleška književnost; literarno prevajanje; prevajanje; slovenščina